Apache Spark 2 : Data Processing and Real-Time Analytics : Master complex big data processing, stream analytics, and machine learning with Apache Spark /: Data Processing and Real-Time Analytics : Master complex big data processing, stream analytics, and machine learning with Apache Spark. (2018) - Kienzler, Romeo; Karim, Md. Rezaul; Alla, Sridhar; Amirghodsi, Siamak; Rajendran, Meenakshi; Hall, Broderick; Mei, Shuen
No abstract available